Approach to iatrogenic colon perforations due to colonoscopy: A retrospective cohort study - Kara, Yasin (Journal of Surgery and Medicine, 2019)
Aim: Iatrogenic colonic perforation (ICP) is a serious complication that can increase mortality and morbidity in patients undergoing therapeutic or diagnostic colonoscopy. The aims of this study are to (1) evaluate the underlying mechanisms of ICPs; (2) discuss the ideal treatment approach and period between onset and treatment; (3) review the current literature regarding the management of ICPs and (4) share our experiences as a single tertiary center. Methods: Patients who underwent colonoscopy between January 2012 and March 2019 at Kanuni Sultan Süleyman Training and Research Hospital’s Endoscopy Unit were reviewed retrospectively. Interventions during which ICPs occurred were documented and analyzed. Results: Between January 2012 and March 2019, 9857 patients underwent colonoscopy and 1320 patients underwent rectosigmoidoscopy at our center. Ten of these procedures were associated with perforation. The perforation rates were 0.06% and 0.23% in diagnostic and therapeutic colonoscopies respectively. The most frequent localizations of perforation were (a) Rectosigmoid junction (30%) (b) Sigmoid colon (30%) (c) Descending colon (20%) and (d) Transvers colon (10% (e) Cecum (10%). Managements included surgical treatment in eight patients two of whom were operated with late laparotomy, endoscopic clipping of perforation and conservative management in one patient, and conservative treatment in one patient. There was no mortality and eight patients discharged uneventfully but one of remaining two patients had acute hepatitis, one had enterocutaneous fistula. Conclusion: Iatrogenic colonic perforations are rare but most serious complications of colonoscopy procedures. Especially, special attention should be given to older and comorbid patients receiving therapeutic procedures during colonoscopy. High risk patients and their families must be informed about this complication. Difficult and tough colonoscopies should be monitored closely at least 24 hours as early diagnosis is vital for treatment. Comorbidities, age, general condition of patient, the size and location of the perforation, and the time interval between onset and diagnosis should be evaluated, and the treatment procedure should be planned. Conservative management, endoscopic clipping, laparoscopic or open operations from primary repair to Hartmann’s procedure can be used, decision should be made on a case by case basis.